KERINDUAN YANG MENDALAM PADA PUISI PERAYAAN KESENDIRIAN KARYA TONI LESMANA: KAJIAN SEMIOTIKA RIFFATERRE - Risma Tiyasti Ningrum (Balai Bahasa Sumatera Utara, 2022)
Semiotics is a science in the field of literature discusses the signs and meanings contained in literary works. One of them is Michael Riffaterre's semiotics. In Riffaterre's theory of semiotics, the meaning of signs in a literary work is the task of its reader. This study focuses on explaining the impatience of expression, heuristic and hermenetic readings, matrices, and also hypograms in a poem entitled Perayaan Kesendirian written by Toni Lesmana. This article aims to understand and interpret Toni Lesmana ‘s poem, Perayaan Kesendirian, which was published on Basabasi.co on June 8, 2021, based on Riffaterre's semiotic theory. Research with the object of the poem entitled Perayaan Kesendirian was carried out because the meaning contained behind the string of arrays and diction in the poem seemed to be conveyed well to the author, in order that the research carried out could give an idea of meaning to the reader. This article is a qualitative research using descriptive methods, with literature review. The result obtained is the meaning of poetry obtained based on the unsustainability of expression with the discovery of several majas, and also ambiguous words, heuristic and hermeneutic readings that describe an array of poems, matrices, and hypograms that contain the overall meaning of longing in poetry. With the results obtained through Riffaterre's Semiotic theory, the meaning in the poem Perayaan Kesendirian can be better understood, namely about the longing experienced by the author or the character of Aku in the poem. The benefits obtained from this research are a good understanding and meaning of poetry for readers, readers are also expected to be able to interpret poetry with Riffaterre's semiotic theory, and of course this research is expected to be a good reference source in literary teaching.